Immunomodulatory effects of gut microbiota on vaccine efficacy against respiratory pathogens - Xue, Li; Wang, Chunhua; Liu, Chuanyu (Frontiers in Immunology, 2025)
The outbreaks of respiratory pathogens like severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) and influenza virus (IV) have heightened the demand for highly effective vaccines that provide strong and durable immunity in human populations. However, immune responses to vaccination vary significantly among individuals and populations. Recent studies have demonstrated that the gut microbiota play an essential role in regulating respiratory pathogens vaccination-induced immune responses through the systemic effects of gut-lung axis on distant organs, the lungs. In this review, we first synthesize the changes in gut microbiota composition and immune responses that occur during respiratory pathogen infections and vaccination. Then, we discuss the underlying immunological mechanisms of bidirectional immunomodulatory effects between gut microbiota and vaccines. Finally, we explore the strategies for designing next-generation vaccines against respiratory pathogens in term of gut microbiota-mediated immunological pathway.